2002
DOI: 10.1124/jpet.300.2.688
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Inhibitors Enhance Saturable Uptake of Idarubicin in Rat Heart: Pharmacokinetic/Pharmacodynamic Modeling

Abstract: Little is known about cardiac uptake kinetics of idarubicin, including a possible protective role of P-glycoprotein (Pgp)-mediated transport. This study therefore investigated uptake and negative inotropic action of idarubicin in the single-pass isolated perfused rat heart by using a pharmacokinetic/pharmacodynamic modeling approach. Idarubicin was administered as a 10-min constant infusion of 0.5 mg followed by a 70-min washout period in the absence and presence of the Pgp antagonists verapamil or amiodarone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…The active transport with Michaelis-Menten type kinetics is characterized by the apparent maximal transport rates V max,12 and the apparent Michaelis constant K M,12 , and the k ij denote first order rate constants describing passive intercompartmental transport. Since the time course IDA 2 (t) was closely related to its pharmacodynamics (negative inotropy), it has been suggested that Compartment 2 reflects distribution in cardiomyocytes (Weiss and Kang, 2002). The rate constant k 24 accounts for cellular sequestration (irreversible binding and/or conversion to IDA aglycone).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The active transport with Michaelis-Menten type kinetics is characterized by the apparent maximal transport rates V max,12 and the apparent Michaelis constant K M,12 , and the k ij denote first order rate constants describing passive intercompartmental transport. Since the time course IDA 2 (t) was closely related to its pharmacodynamics (negative inotropy), it has been suggested that Compartment 2 reflects distribution in cardiomyocytes (Weiss and Kang, 2002). The rate constant k 24 accounts for cellular sequestration (irreversible binding and/or conversion to IDA aglycone).…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the model and the parameters accounting for the disposition of IDA were then fixed in fitting an extended model to the outflow concentration profile of the formed IDOL. Thereby, we used the ADAPT II software package (D'Argenio and Schumitzky, 1997) and a modeling methodology that has been described in detail previously (Weiss and Kang, 2002). Since especially for nonlinear systems the information content of one experiment may be insufficient to resolve the parameters into a unique set of most probable values, we took advantage of the fact that three data sets stem from different but related experiments, the modeling function of which shares one or more parameters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations